Curcumin Nanoparticles Attenuate Lipotoxic Injury in Cardiomyocytes Through Autophagy and Endoplasmic Reticulum Stress Signaling Pathways - Yue Gu; Huan Xia; Xiao Chen; Jing Li (Frontiers Media S.A., 2021)
Although curcumin (CUR) has many advantages, its hydrophobicity and instability limit its application. In this study, the anti-lipotoxic injury activity of CUR-loaded nanoparticles (CUR-NPs) and the corresponding mechanism were examined in palmitate (PA)-treated cardiomyocytes. An amphiphilic copolymer was selected as the vehicle material, and CUR-NPs with suitable sizes were prepared under optimized conditions. Cellular uptake was examined by confocal laser scanning microscopy, and cell proliferation inhibition rate was measured using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetra bromide (MTT) assay. The terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) assay was used to detect cell apoptosis. The protein expression was detected by western blot. Exposure to PA reduces the proliferation of cardiomyocytes, but this effect was strongly reversed by CUR-NPs. In addition, our data showed that CUR-NPs strongly inhibited cell apoptosis in PA-treated cardiomyocytes. Furthermore, CUR-NPs remarkably increased the expression of LC3-II, as well as inhibited the expression of p-PERK, p-eIF2α, and ATF4 in PA-treated cardiomyocytes. Salubrinal (an eIF2α inhibitor) blocked the protective effect of CUR-NPs against PA-induced cardiomyocyte injury. Our results suggested that CUR-NPs can activated the autophagy pathway and protect myocardial cells from apoptosis, and these effects may be mediated by the eIF2α-related endoplasmic reticulum stress signaling pathway.